prev

next

out of 33

View

215Download

0

Embed Size (px)

8/8/2019 18686025 Laplace Transforms

1/33

S. Boyd EE102

Lecture 3The Laplace transform

denition & examples

properties & formulas

linearity the inverse Laplace transform time scaling exponential scaling time delay derivative integral multiplication by t convolution

31

8/8/2019 18686025 Laplace Transforms

2/33

Idea

the Laplace transform converts integral and differential equations intoalgebraic equations

this is like phasors, but

applies to general signals, not just sinusoids

handles non-steady-state conditions

allows us to analyze

LCCODEs

complicated circuits with sources, Ls, Rs, and Cs complicated systems with integrators, differentiators, gains

The Laplace transform 32

8/8/2019 18686025 Laplace Transforms

3/33

Complex numbers

complex number in Cartesian form: z = x + jy

x = z, the real part of z

y = z, the imaginary part of z

j = 1 (engineering notation); i = 1 is polite term in mixedcompanycomplex number in polar form: z = re j

r is the modulus or magnitude of z is the angle or phase of z

exp( j) = cos + j sin

complex exponential of z = x + jy :

ez = ex + jy = ex ejy = ex (cos y + j sin y)

The Laplace transform 33

8/8/2019 18686025 Laplace Transforms

4/33

The Laplace transform

well be interested in signals dened fort 0the Laplace transform of a signal (function) f is the function F = L(f )dened by

F (s) =

0f (t)e st dt

for those sC for which the integral makes sense

F is a complex-valued function of complex numbers s is called the (complex) frequency variable , with units sec

1; t is calledthe time variable (in sec); st is unitless

for now, we assume f contains no impulses at t = 0common notation convention: lower case letter denotes signal; capitalletter denotes its Laplace transform, e.g. , U denotes L(u), V in denotesL(vin ), etc.The Laplace transform 34

8/8/2019 18686025 Laplace Transforms

5/33

Example

lets nd Laplace transform of f (t) = et :

F (s) =

0et e st dt =

0e(1 s ) t dt =

11 s

e(1 s ) t

0=

1s 1

provided we can say e(1 s ) t 0 as t , which is true for s > 1:e(1 s ) t = e j ( s ) t

=1e(1 s ) t = e(1 s ) t

the integral dening F makes sense for all sC with s > 1 (theregion of convergence of F )

but the resulting formula for F makes sense for all s

C except s = 1

well ignore these (sometimes important) details and just say that

L(et ) =

1

s 1The Laplace transform 35

8/8/2019 18686025 Laplace Transforms

6/33

More examples

constant: (or unit step) f (t) = 1 (for t 0)

F (s) =

0e st dt =

1

se st

0=

1

s

provided we can say e st 0 as t , which is true for s > 0 since

e st = e j ( s ) t

=1e ( s ) t = e ( s ) t

the integral dening F makes sense for all s with s > 0

but the resulting formula for F makes sense for all s except s = 0

The Laplace transform 36

8/8/2019 18686025 Laplace Transforms

7/33

sinusoid: rst express f (t) = cos t as

f (t) = (1 / 2)ejt + (1 / 2)e jt

now we can nd F as

F (s) =

0e st (1/ 2)ejt + (1 / 2)e jt dt

= (1 / 2)

0 e( s + j ) t

dt + (1 / 2)

0 e( s j ) t

dt

= (1 / 2)1

s j+ (1 / 2)

1s + j

=s

s2 + 2

(valid for s > 0; nal formula OK fors = j)

The Laplace transform 37

8/8/2019 18686025 Laplace Transforms

8/33

powers of t : f (t) = tn (n 1)well integrate by parts, i.e. , use

ba u(t)v (t) dt = u(t)v(t)b

a b

av(t)u (t) dt

with u(t) = tn , v (t) = e st , a = 0 , b = F (s) =

0tn e st dt = tn e

st

s

0+

ns

0tn 1e st dt

= ns L(t

n 1)

provided tn e st 0 if t , which is true for s > 0applying the formula recusively, we obtain

F (s) =n!

sn +1

valid for s > 0; nal formula OK for alls = 0The Laplace transform 38

8/8/2019 18686025 Laplace Transforms

9/33

Impulses at t = 0

if f contains impulses at t = 0 we choose to include them in the integraldening F :

F (s) =

0f (t)e st dt

(you can also choose to not include them, but this changes some formulaswell see & use)

example: impulse function, f =

F (s) =

0(t)e st dt = e st t =0 = 1

similarly for f = (k ) we have

F (s) =

0(k ) (t)e st dt = ( 1)k

dk

dtke st

t =0= sk e st t =0 = s

k

The Laplace transform 39

8/8/2019 18686025 Laplace Transforms

10/33

Linearity

the Laplace transform is linear : if f and g are any signals, and a is anyscalar, we have

L(af ) = aF, L(f + g) = F + Gi.e. , homogeneity & superposition hold

example:

L 3(t) 2et = 3L((t)) 2L(et )

= 3 2

s 1=

3s 5s 1

The Laplace transform 310

8/8/2019 18686025 Laplace Transforms

11/33

One-to-one property

the Laplace transform is one-to-one : if L(f ) = L(g) then f = g(well, almost; see below)

F determines f inverse Laplace transform L 1 is well dened(not easy to show)example (previous page):

L 1 3s 5

s 1= 3 (t) 2et

in other words, the only function f such that

F (s) =3s 5s 1

is f (t) = 3 (t)

2et

The Laplace transform 311

8/8/2019 18686025 Laplace Transforms

12/33

what almost means: if f and g differ only at a nite number of points(where there arent impulses) then F = G

examples:

f dened as f (t) = 1 t = 20 t = 2has F = 0

f dened asf (t) = 1/ 2 t = 01 t > 0

has F = 1 /s (same as unit step)

The Laplace transform 312

8/8/2019 18686025 Laplace Transforms

13/33

Inverse Laplace transform

in principle we can recoverf from F via

f (t) =1

2j + j

j F (s)est ds

where is large enough that F (s) is dened for s

surprisingly, this formula isnt really useful!

The Laplace transform 313

8/8/2019 18686025 Laplace Transforms

14/33

Time scaling

dene signal g by g(t) = f (at ), where a > 0; then

G(s) = (1 /a )F (s/a )

makes sense: times are scaled by a, frequencies by 1/a

lets check:

G(s) =

0 f (at )e

st dt = (1 /a )

0 f ( )e

(s/a ) d = (1 /a )F (s/a )

where = at

example: L(et) = 1 / (s 1) so

L(eat ) = (1 /a )1

(s/a ) 1=

1s a

The Laplace transform 314

8/8/2019 18686025 Laplace Transforms

15/33

Exponential scaling

let f be a signal and a a scalar, and dene g(t) = eat f (t); then

G(s) = F (s a)

lets check:

G(s) =

0 e

st eat f (t) dt =

0 e

( s

a ) t f (t) dt = F (s a)

example:

L(cos t) = s/ (s2 + 1) , and hence

L(e t cos t) =

s + 1(s + 1) 2 + 1

=s + 1

s2 + 2 s + 2

The Laplace transform 315

8/8/2019 18686025 Laplace Transforms

16/33

Time delay

let f be a signal and T > 0; dene the signal g as

g(t) = 0 0 t < T f (t T ) t T (g is f , delayed by T seconds & zero-padded up to T )

ttt = T

f ( t ) g ( t )

The Laplace transform 316

8/8/2019 18686025 Laplace Transforms

17/33

then we have G(s) = e sT F (s)

derivation:

G(s) =

0e st g(t) dt =

T e st f (t T ) dt

=

0e s ( + T ) f ( ) d

= e sT F (s)

The Laplace transform 317

8/8/2019 18686025 Laplace Transforms

18/33

example: lets nd the Laplace transform of a rectangular pulse signal

f (t) = 1 if a t b0 otherwisewhere 0 < a < b

we can write f as f = f 1 f 2 wheref 1(t) =

1 t a0 t < a f 2(t) =1 t b0 t < b

i.e. , f is a unit step delayed a seconds, minus a unit step delayed b seconds

hence

F (s) = L(f 1) L(f 2)=

e as e bs

s

(can check by direct integration)

The Laplace transform 318

8/8/2019 18686025 Laplace Transforms

19/33

Derivative

if signal f is continuous at t = 0 , then

L(f ) = sF (s) f (0)

time-domain differentiation becomes multiplication by frequencyvariable s (as with phasors) plus a term that includes initial condition ( i.e. , f (0) )

higher-order derivatives: applying derivative formula twice yields

L(f ) = sL(f ) f (0)= s(sF (s) f (0)) f (0)= s2F (s) sf (0) f (0)

similar formulas hold for

L(f (k ) )

The Laplace transform 319

8/8/2019 18686025 Laplace Transforms

20/33

examples

f (t) = et , so f (t) = et and

L(f ) = L(f ) =1

s 1using the formula, L(f ) = s(

1s 1

) 1, which is the same

sin t =

1

ddt cos t, so

L(sin t) = 1

ss

s2 + 2 1 =

s2 + 2

f is unit ramp, so f is unit step

L(f ) = s1s2 0 = 1/s

The Laplace transform 320

8/8/2019 18686025 Laplace Transforms

21/33

derivation of derivative formula: start from the dening integral

G(s) =

0f (t)e st dt

integration by parts yields

G(s) = e st f (t)

0

0f (t)(se

st ) dt

= limt f (t)e st

f (0) + sF (s)

for s large enough the limit is zero, and we recover the formula

G(s) = sF (s) f (0)

The Laplace transform 321